Exploring the metabolic and physiological roles of HQT in S. lycopersicum by gene editing - D’Orso, Fabio; Hill, Lionel; Appelhagen, Ingo; Lawrenson, Tom; Possenti, Marco; Li, Jie; Harwood, Wendy; Morelli, Giorgio; Martin, Cathie (Frontiers in Plant Science, 2023)
The most abundant phenolic compound in Solanaceous plants is chlorogenic acid (CGA), which possesses protective properties such as antimicrobial and antioxidant activities. These properties are particularly relevant when plants are under adverse conditions, such as pathogen attack, excess light, or extreme temperatures that cause oxidative stress. Additionally, CGA has been shown to absorb UV-B light. In tomato and potato, CGA is mainly produced through the HQT pathway mediated by the enzyme hydroxycinnamoyl-CoA:quinate hydroxycinnamoyl transferase. However, the absence of natural or induced mutants of this gene has made it unclear whether other pathways contribute to CGA production and accumulation. To address this question, we used CRISPR technology to generate multiple knock-out mutant lines in the tomato HQT gene. The resulting slhqt plants did not accumulate CGA or other caffeoylquinic acids (CQAs) in various parts of the plant, indicating that CQA biosynthesis depends almost entirely on the HQT pathway in tomato and, likely, other Solanaceous crops. We also found that the lack of CGA in slhqt plants led to higher levels of hydroxycinnamoyl-glucose and flavonoids compared to wild-type plants. Gene expression analysis revealed that this metabolic reorganization was partly due to flux redirection, but also involved modulation of important transcription factor genes that regulate secondary metabolism and sense environmental conditions. Finally, we investigated the physiological role of CGA in tomato and found that it accumulates in the upper epidermis where it acts as a protector against UV-B irradiation.